2021
DOI: 10.1097/bot.0000000000002046
|View full text |Cite
|
Sign up to set email alerts
|

Do Early Weight-Bearing and Range of Motion Affect Outcomes in Operatively Treated Ankle Fractures: A Systematic Review and Meta-Analysis

Abstract: Objectives: This systematic review was performed to answer the following questions: (1) Does early weight-bearing (WB) after ankle fracture (AF) open reduction internal fixation (ORIF) affect outcomes? (2) Does early WB after AF ORIF cause an increase in complications? (3) Does early ankle motion after AF ORIF affect outcomes? and (4) Does early ankle motion after AF ORIF cause an increase in complications?Data Sources: Articles from 1970 to 2020 were found using the PubMed database. Study Selection:Level I st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(271 reference statements)
4
10
0
1
Order By: Relevance
“…It must also be stated that we excluded patients with uncontrolled diabetes and open ankle fractures, as such, our findings cannot be extrapolated to these patient populations with potential for increased risk of wound complication. In a meta-analysis by Sernandez et al, 18 there were differences in outcomes and no differences related to wound complications once stable fixation was achieved. Regarding time to fracture union and hardware failure, our study demonstrated no difference in time to fracture union between the mobilization groups.…”
Section: Discussionmentioning
confidence: 93%
“…It must also be stated that we excluded patients with uncontrolled diabetes and open ankle fractures, as such, our findings cannot be extrapolated to these patient populations with potential for increased risk of wound complication. In a meta-analysis by Sernandez et al, 18 there were differences in outcomes and no differences related to wound complications once stable fixation was achieved. Regarding time to fracture union and hardware failure, our study demonstrated no difference in time to fracture union between the mobilization groups.…”
Section: Discussionmentioning
confidence: 93%
“…A recent meta-analysis from New York (New York, USA) evaluated level I studies of adults with operatively treated ankles, and the effects of early weightbearing on complications and outcomes. 11 The analysis included 1,130 patients across 20 studies, two of which reported functional outcome scores. In these studies, a total of 356 patients had early weightbearing, 178 of these in a cast.…”
Section: Ankle Fractures: Can We Weightbear Them Early? X-refmentioning
confidence: 99%
“…11 Findings for complication rate also varied, with the 2021 review reporting increased complications after early ankle mobilization, whereas the 2015 review reporting no differences between early and late weight-bearing. 11,13 These reviews focused on the effect of specific postoperative strategies on patient outcomes but did not detail the range of postoperative strategies available nor offer details on interventions such as the exact timing and percentage/amount of weight-bearing, use of mobility aids, or other therapy modalities that can influence patient outcomes and inform clinical decision-making. Thus, a comprehensive review that described the current postoperative practices by detailing the specific characteristics of published current ankle postoperative rehabilitation strategies and their effectiveness is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 most recent systematic reviews and meta-analyses on postoperative recommendations in ankle fractures were published in 2015 and 2021. These systematic reviews investigated specified types of postoperative strategies; the 2021 review reported no difference in outcomes between early and late weight-bearing , 13 whereas the 2015 review reported better outcomes for those performing ankle exercises compared with immobilization . 11 Findings for complication rate also varied, with the 2021 review reporting increased complications after early ankle mobilization, whereas the 2015 review reporting no differences between early and late weight-bearing.…”
Section: Introductionmentioning
confidence: 99%